2009
DOI: 10.1128/jb.01804-08
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Prophages in Dominant Staphylococcus aureus Clonal Lineages

Abstract: Temperate bacteriophages play an important role in the pathogenicity of Staphylococcus aureus, for instance, by mediating the horizontal gene transfer of virulence factors. Here we established a classification scheme for staphylococcal prophages of the major Siphoviridae family based on integrase gene polymorphism. Seventy-one published genome sequences of staphylococcal phages were clustered into distinct integrase groups which were related to the chromosomal integration site and to the encoded virulence gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
275
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(298 citation statements)
references
References 33 publications
18
275
0
Order By: Relevance
“…Lysogeny is a symbiotic strategy in which the prophage has a stable niche in the host genome, and protects its host against attack by other phages (Goerke et al, 2009), through co-immunity, CRISPR interference (Barrangou et al, 2007;Marraffini and Sontheimer, 2008) or expression of RM activities that inhibit interspecies and even intraspecies gene transfers (Barrangou et al, 2007;Park et al, 1999). This may be particularly relevant for the CC398 lineage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lysogeny is a symbiotic strategy in which the prophage has a stable niche in the host genome, and protects its host against attack by other phages (Goerke et al, 2009), through co-immunity, CRISPR interference (Barrangou et al, 2007;Marraffini and Sontheimer, 2008) or expression of RM activities that inhibit interspecies and even intraspecies gene transfers (Barrangou et al, 2007;Park et al, 1999). This may be particularly relevant for the CC398 lineage.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus is highly lysogenic. S. aureus phages are double-stranded DNA phages belonging to the Siphoviridae family (Goerke et al, 2009). Comparative genomic analyses have revealed substantial diversity of these phages; nevertheless, they also display extensive mosaicism, with genes organized into functional modules that are frequently exchanged between phages (Kahankova et al, 2010;Xia and Wolz, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome analyses of many genera, such as Bacillus, Enterococcus, Listeria, Mannheimia, Paracoccus, Staphylococcus and Streptococcus revealed that polylysogeny is a common phenomenon (Dziewit et al, 2014a;Goerke et al, 2009;Niu et al, 2015). Recently, we have also identified a polylysogenic Sinorhizobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Although temperate phages of S. aureus are more widely known [53,54], due to the potential problems of lysogeny and toxic gene transfer, its therapeutic use is limited [55]. Hence, the present article on efficacy of two lytic bacteriophages of staphylococcus namely Phage K and 44AHJD on nasal decolonization of Staphylococcus aureus in mice nares is relevant and valuable.…”
Section: Evaluation Of Phage Efficacy In Vivomentioning
confidence: 99%